Dark spring essays on the ideological roots of Malaysia's GE-13 - Azly Rahman (Strategic Information and Research Development Centre, 2013)
Azly Rahman's Dark Spring is a book about evolution. He has strived to take us out of the shadows of Plato's cave, into the freedom of an emancipated Malaysian society free of hegemony, repression, and suppression. However, as Azly has eluded, there is so much to do in Malaysia if the country is going to re-vegetate the barren lands that have been stripped for decades, and regenerate the Malaysian mind to face the emerging national and global challenges ahead.